2020
DOI: 10.1186/s40813-020-00148-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mycoplasma hyopneumoniae and porcine circovirus 2 commercial vaccines efficacy when applied separate or combined under experimental conditions

Abstract: Background Mycoplasma hyopneumoniae (Mhyo) and Porcine circovirus 2 (PCV-2) are two of the most significant infectious agents causing economic losses in the weaning to slaughter period. Due to their similar vaccination age, the objective of this study was to assess the efficacy of two already existing Mhyo (Hyogen®) and PCV-2 (Circovac®) vaccines when administered separately or combined (RTM) by means of Mhyo or PCV-2 experimental challenges. Results Seven groups of animals were included in the study, being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
3
4
1
Order By: Relevance
“…The reason for this observation is unknown but could be explained by the intrinsic composition of both PCV-2 vaccines compared in our study. Means S:P ratios measured during the trial in pigs vaccinated with Hyogen® and Circovac® mixed were in accordance with one previously published study after inoculation, S:P ratios varied between 0.2 and 0.8 [ 27 ]. We detected PCV-2 DNA in blood from unvaccinated pigs from 18 weeks of age but we didn’t observe seroconversion between 18 weeks of age and the end of the trial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The reason for this observation is unknown but could be explained by the intrinsic composition of both PCV-2 vaccines compared in our study. Means S:P ratios measured during the trial in pigs vaccinated with Hyogen® and Circovac® mixed were in accordance with one previously published study after inoculation, S:P ratios varied between 0.2 and 0.8 [ 27 ]. We detected PCV-2 DNA in blood from unvaccinated pigs from 18 weeks of age but we didn’t observe seroconversion between 18 weeks of age and the end of the trial.…”
Section: Discussionsupporting
confidence: 89%
“…These results supported the usefulness of this threshold for M. hyopneumoniae serological monitoring in practice in vaccinated pigs. In a previous study, vaccination against M. hyopneumoniae resulted in a significantly higher percentage of seropositive animals 3 weeks after vaccination [ 27 ], whereas in our trial a significant increase in the percentage of seropositive pigs was observed 6 weeks after vaccination. In both vaccinated groups, mean S: P values were similar at all sampling times, but no correlation between antibody titers and protection against the infection is demonstrated to date.…”
Section: Discussioncontrasting
confidence: 78%
“…This may have been explained by the low amount of pigs with pathological changes and abnormal clinical signs after challenge in both groups. Similar PCV2 subclinical infection outcome has been previously described in PCV2 experimental inoculations which is consequent to that described in previous PCV2 experimental infections [ 24 , 45 ]. Finally, criteria for prevention/reduction in viremia, fecal shedding, and PCV2 antigen in lymphoid tissues (IHC) were met as those variables presented a value >0 on the lower 95% confidence interval for the prevented fraction.…”
Section: Discussionsupporting
confidence: 88%
“…Mhyo commercial vaccines are mostly applied to piglets as a single dose between the first and the third weeks of age and aim to prevent the effects of Mhyo occurring after weaning [ 23 ]. As a consequence, due to the parallelisms seen on both infections and that vaccination of both pathogens takes place in piglets around the same age, combined vaccination has been explored since 2010 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of M. hyopneumoniae, piglets are thought to be firstly exposed to the pathogen during the lactation period; thus, the vaccination against this pathogen should also be performed in the first few weeks of life [7]. Therefore, applying vaccines that are simultaneously protective for both PCV2 and M. hyopneumoniae is epidemiologically justified by the following reasons: first, their efficacy is equivalent to that obtained when they are administered separately [10,11]; second, this strategy offers advantages to swine producers such as reducing the labor costs, the number of manipulations that the animals undergo and the risk of pathogen transmission through needles; third, this lower need for animal manipulation and injection leads to an improvement of piglet welfare.…”
Section: Introductionmentioning
confidence: 99%